Plant Use in Spiritual Communication With Souls by An Animistic Community in Siberut, Indonesia - Herwig Zahorka (The Ethnobiological Society of Indonesia, 2004)
This article present plant use in spiritual communication with souls by an animistic community in Siberut. Based on that animistic belief the Mentawaians consider ills and diseases being created by the malicious bajou of an animated being or object which has frightened or startled the human's simagere or, because the human has disobeyed social taboos. Curing rituals are performed by the kerey (shamans) and by special healers using the helpful bajou of selected « medicinal » plants.